2012
DOI: 10.2134/agronj2011.0390
|View full text |Cite
|
Sign up to set email alerts
|

Bermudagrass and Seashore Paspalum Establishment from Seed Using Differing Irrigation Methods and Water Qualities

Abstract: Two approaches, irrigation with impaired waters, and use of subsurface drip irrigation, have been identifi ed as strategies to reduce the use of potable water for landscape irrigation. A study was conducted at New Mexico State University in Las Cruces in 2008 and 2009 to investigate the establishment of Princess 77 bermudagrass [Cynodon dactylon (L.)] and Sea Spray seashore paspalum [Paspalum vaginatum (Sw.)] seeded in March (dormant) or June (traditional). Th e grasses were irrigated at 98% reference evapotra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
55
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 36 publications
(66 citation statements)
references
References 22 publications
9
55
0
Order By: Relevance
“…Salinity was also not problematic when saline water was applied through SDI. Although our results confirm those of Sevostianova et al (2011a) and Schiavon et al (2012Schiavon et al ( , 2013, who documented increased salinity levels in soil irrigated through SDI, quality and NDVI of subsurface-irrigated turf did not differ for two of the 3 yr between those given saline water and those receiving potable water. These results suggest that it is possible to maintain acceptable quality in warm-season species in an arid environment with deficit irrigation (50% ET OS ) and saline water.…”
Section: Discussionsupporting
confidence: 64%
“…Salinity was also not problematic when saline water was applied through SDI. Although our results confirm those of Sevostianova et al (2011a) and Schiavon et al (2012Schiavon et al ( , 2013, who documented increased salinity levels in soil irrigated through SDI, quality and NDVI of subsurface-irrigated turf did not differ for two of the 3 yr between those given saline water and those receiving potable water. These results suggest that it is possible to maintain acceptable quality in warm-season species in an arid environment with deficit irrigation (50% ET OS ) and saline water.…”
Section: Discussionsupporting
confidence: 64%
“…However, only few studies have examined whether or not it is possible to apply standard establishment and maintenance practices on SDI‐irrigated turf. Schiavon, Leinauer, Serena, Sallenave, and Maier (, ) and Serena, Leinauer, Schiavon, Maier, and Sallenave () reported successful establishment of both warm‐ and cool‐season turfgrasses from seed and sod using SDI. On the other hand, SDI resulted in increased salt concentration in the root zone compared to irrigation with an OSI when used in combination with saline water (Ganjegunte, Leinauer, Schiavon, & Serena, ; Schiavon et al., , ; Sevostianova, Leinauer, Sallenave, Karcher, & Maier, ,b).…”
Section: Introductionmentioning
confidence: 98%
“…The effect of different climatic conditions (especially air and soil temperature) on green‐up and carbohydrate content has been reported by Schiavon et al. (), Schiavon et al. () and Rimi et al.…”
Section: Resultsmentioning
confidence: 76%
“…In summary, the authors concluded that in a transitional arid or semi‐arid environment, warm‐season grasses are generally more salt tolerant and better adapted to the prevalent multiple environmental stresses than cool‐season grasses. Particularly when saline irrigation water is applied from the subsurface, cyclic changes in root zone salinity are more dominant than in root zones irrigated with an OSI system (Ganjegunte, Leinauer, Schiavon, & Serena, ; Schiavon, Leinauer, Serena, Sallenave, & Maier, ; Schiavon, Leinauer, Sevostianova, Serena, & Maier, ; Sevostianova et al., ,). For these reasons, salt‐tolerant species such as bermudagrass ( Cynodon dactylon L.), seashore paspalum ( Paspalum vaginatum Sw.), zoysiagrass ( Zoysia spp) and inland saltgrass ( Distichlis spicata (L.) Greene) are best suited when saline water and subsurface drip irrigation are used.…”
Section: Introductionmentioning
confidence: 99%